Verbal Comprehension Ability in Aphasia: Demographic and Lexical Knowledge Effects - Panagiotis G. Simos; Dimitrios Kasselimis; Constantin Potagas; Ioannis Evdokimidis (Behavioural Neurology)
Background. Assessment of sentence-level auditory comprehension can be performed with a variety of tests varying in response requirements. A brief and easy to administer measure, not requiring an overt verbal or a complex motor response, is essential in any test battery for aphasia. Objective. The present study examines the clinical utility of receptive language indices for individuals with aphasia based on the Comprehension of Instructions in Greek (CIG), a variant of the Token Test, and the Greek version of PPVT-R. Methods. Normative data from a large community sample of Greek adults aged 46–80 years was available on both measures. A word-level-independent measure of auditory comprehension was computed as the standard score difference between the two tests and used to compare patients with and without comprehension deficits as indicated by their Boston Diagnostic Aphasia Examination profile. Results and Conclusions. Indices of internal consistency and test-retest reliability were very good. Education and age effects on performance were significant, with the former being stronger. The potential clinical utility of differential ability indices (contrasting sentence- and word-level auditory comprehension tests) is discussed.